Assessment of Compliance and Barriers to Spectacles Use in Prescribed Patients - Hira Ali, Mohammad Parvez, Muhammad Ayub Khan, Muhammad Irfan, Aimal Khan, Mohammad Afzal Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: One cause of preventable visual impairment in the world is the uncorrected refractive error. Even though the simplicity and low costs of spectacles offer a low-cost issue, adherence to the use of spectacles is still not optimal because of many social, economic, and behavioral considerations. Objective: To determine adherence and the obstacles to the use of spectacles among the patients who were prescribed with spectacles in a tertiary care hospital in Quetta, Pakistan. Methods: The proposed study is a cross-sectional descriptive study conducted at Helpers Eye Hospital, Quetta, between April 2022 and April 2023. Non-probability consecutive sampling was used to enroll 200 patients of 6 years and older that had received spectacles at least three months before the study. A structured questionnaire was used to measure frequency of spectacle use and perceived barriers and this was used to collect the data. The compliance was divided into regular use, occasional use and non-use. The SPSS version 26 was used to analyze data. They were tested using chi-square test, and a p ≤ 0.05 was taken to be statistically significant. Results: The average age of the respondents was 18.66 years with 56.0 percent being males and 44.0 percent being females. One hundred and eighty four (118) patients (59.0) reported regular use of the spectacle and 82 (41.0) were non-compliant. Cosmetic concerns (26.8%), discomfort or headache (22.0%), social stigma (18.3%), and forgetfulness (15.9%), have been most frequently reported. The compliance was found to be closely related to age (p = 0.021), time since prescription (p = 0.009), and perceived visual benefit (p = 0.001), but not gender. Conclusion: There is a significant percentage of non-adherence to regular spectacle use in the group of prescribed patients because of barriers that can be changed. Individualized counseling, better patient education, and community education are necessary to increase compliance and preventable visual impairment. Keywords: Spectacle compliance; Refractive error; Visual impairment; Barriers; Patient adherence; Pakistan.